The Development of Domino Nusantara Conservation Media for Students IV Grade Elementary School of Purwoyoso 01 Semarang - Melina, Farid Ahmadi, Veni (Elementary School Teacher, 2017)
unoptimal to use learning media, then still centered on teachers, lack of model variation and methods in learning, low enthusiasm of student. The formulation of the problem in this research is how the development, feasibility and effectiveness of Donat Conservation as a learning media to improve the learning result of sosial studies in the cognitive domain in the fourth grade elementary school of Purwoyoso 01 Semarang. The research aims to develop learning media, know the feasibility of media, and to know the effectiveness of Donat Conservation media on the learning results of IPS in the cognitive domain for Cultural Diversity of Nations matter in the fourth grade elementary school of Purwoyoso 01 Semarang. This research type is Research and Development (R and D) with Borg and Gall model. Data analysis techniques, including product data analysis, preliminary data analysis and final data analysis. The results show that the percentage gained from material experts is 89% (very feasible) and the percentage gained by media experts is 84.7% (very feasible). Results of small group experiments have improved with the acquisition of understanding in moderate criteria. It is also shown on the average posttest result of large group, that is 88,67, compared to average pretest which only 69,67 with acquisition of understanding in medium criteria (NGain = 0,63). And the result of t test is 21,651 which means there is difference of learning result with positive response from student and teacher. So it can be concluded that Donat Conservation media is feasible to be used and effective to improve the result of sosial studies in cognitive domain.